IMPLEMENTATION CERTAINTY FACTOR METHODS TO DIAGNOSE DISEASES IN PALM PLANTS - Ikhanto, M Nur; Sutomo, Budi; kurniawati, Desi (STMIK DHARMA WACANA, 2020)
Mustard is a type of vegetable that is easy to cultivate. Mustard plants also include plants that are susceptible to diseases, such as earthworms, armyworms, leaf destroyers, club roots, and leaf spots. The limited knowledge of farmers about the types of diseases that attack the mustard plant causes mishandling which results in crop failure. The purpose of this research is to build an expert system that can help farmers diagnose the types of diseases that attack the mustard plant. The method used in building this expert system is the Certainty Factor which can find out certainty based on the evidence and judgment of an expert. The system is built on a website basis, which in its development uses the Rapid Application Development (RAD) method. The results of the research will provide output in the form of types of diseases that attack mustard plants based on the diagnoses entered by the user and provide ways of handling them.